1991
DOI: 10.1111/j.1442-200x.1991.tb02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Prolapse in Childhood: The Incidence and Clinical Presentations in Different Age Groups

Abstract: To elucidate the incidence and natural history of mitral valve prolapse (MVP) during childhood, we investigated a total of 4,238 children (aged from 1 day to 15 years) classified by age into 4 groups: Group 1 : 1 to 28-day-old full-term normal newborns (n = 108), Group 2: 6 to 18-month-old infants (n = 391), Group 3: 6 to 7-year-old children (n = 2,801), and Group 4: 12 to 15-year-old children (n = 938). The incidence of MVP was determined by videorecorded two-dimensional echocardiography in a double-blind met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…The term FMV comes from surgical and pathologic studies and refers to the expansion of the area of the mitral valve leaflets with elongated chordae tendineae, chordae tendineae rupture and often mitral annular dilatation [2,5,7]. The prevalence of FMV/MVP as defined above in the general population is 2-3% [2,8,9,10,11,12,13]. It is important to separate studies where the diagnosis was based solely on prolapse of the mitral valve without defining if the mitral valve was ‘floppy' or not.…”
Section: Introduction/definitionsmentioning
confidence: 99%
“…The term FMV comes from surgical and pathologic studies and refers to the expansion of the area of the mitral valve leaflets with elongated chordae tendineae, chordae tendineae rupture and often mitral annular dilatation [2,5,7]. The prevalence of FMV/MVP as defined above in the general population is 2-3% [2,8,9,10,11,12,13]. It is important to separate studies where the diagnosis was based solely on prolapse of the mitral valve without defining if the mitral valve was ‘floppy' or not.…”
Section: Introduction/definitionsmentioning
confidence: 99%
“…Interestingly, patients with mitral valve prolapse have a high incidence of autonomic dysfunction, leading to symptoms out of proportion to their degree of mitral valve disease. The incidence of mitral valve prolapse in asymptomatic children increases considerably by age 15 . Various studies have found an overall incidence in children 0–18 years of age of 0.3%, 16 and an incidence in adolescents as high as 5% 15 .…”
Section: Mitral Valve Insufficiency: Causesmentioning
confidence: 99%
“…The incidence of mitral valve prolapse in asymptomatic children increases considerably by age 15 . Various studies have found an overall incidence in children 0–18 years of age of 0.3%, 16 and an incidence in adolescents as high as 5% 15 . In a study of patients known to have mitral valve prolapse, the majority were asymptomatic, and 20% had associated skeletal or connective tissue disease 17 .…”
Section: Mitral Valve Insufficiency: Causesmentioning
confidence: 99%
“…Kliniğimizdeki MVP'li hastaların %20'sinde olduğu gibi göğüs ağrısı genellikle atipik ve nonpesifiktir, anjina pektorise benzemez ve egzersiz ile provake olmaz. Nedeni kesin olarak bilinmemekle birlikte papiller kaslar ve ventrikül duvarı üzerindeki artmış basınca ve koroner arterlerdeki spazma bağlı olarak geliştiği dü-şünülmektedir (16).…”
unclassified